DETERMINATION OF CHEMICALCOMPOSITIONOF MEAT ANDFLOUR FROM GONGGONG SNAIL(Strombus sp.) - Bella Billiant JAK; Mery Sukmiwati; Rahman Karnila (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
AbstrakThis study was aimed to determine the chemical composition of meat and flour from gonggong snail (Strombus sp.)and to determine the yield from flour from gonggong snail. The research method consisted of 2 stages 1) Preparationand chemical analysis of meat from gonggong snail 2) Making flour and chemical analysis of flour snails. The observed parameters were moisture, ash, protein, fat and yield. The results showed that the ehole gonggong snail was the largest proportion in the body shell by 60% among other body parts. Moreover, thechemical composition of fresh meat from gonggong snail 75.05% (wb) moisture, 11.74% (db) ash,79.11% (db) protein and 8.21% (db) fat. Furthermore, the chemical composition of flour from gonggong snailwas 9.75% (wb) moisture, 9.60% (db) ash, 78.33% (db) proteinand 7.19% (db) fat. The flour of gonggong snail had a yield 89,89%. Key: Chemical Composition, Gonggong Snail, Yield.